Ciência e arte: vida-(e)-morte encenada(s) - Janeiro, Artur Rodrigues [UNESP] (2015)
In the present research work the triggering object of explorations and reflections is the plastination, a physical-chemical preservation technique for biological tissues created by the contemporary anatomist Gunther von Hagens, a cadaver manipulator. His products - denominated specimens - can still be considered bodies? living? dead? are they representations of the real anatomical structures? are they in fact preserved? Of a post critic character, this particularly structured research work achieves its intended goals - the following text is in itself a resizing, a testimony of an unprecedented, thought-provoking pathreading, proper to/from the author, who goes beyond his own professional education (not only academic) and expressively walks through Art, Science (Biology/Anatomy) and Education (Human Development; of the subject), promoting cracks that emerge mainly from the shredding of the representation of the world; cracks that also, under small displacements, (re)fit with new contacts, ensuring the visualization of the art-anatomy concept. Cracks that misaligns the rigid plot of the modern scientific thought; that sustains my freedom in this study-act